Comparative analysis of optotypes of Sivtsev, Golovin tables and infrared videonystagmography - Z. I. Mamedov; I. A. Loskutov; E. P. Poruchikova (Oftalʹmologiâ, 2024)
Visiometry is one of the fundamental diagnostic methods for assessing visual acuity, including the evaluation of the effectiveness of eye pathology treatment. Therefore, a precise determination of visual acuity is crucial. For a long time, visual acuity has been determined by reading optotypes on optometric charts (in Russia and the CIS countries, the Sivtsev — Golovin chart is the most widely used). With the advancement of “Eye tracking” technologies and the development of high-frequency and detailed monitors, it has become possible to determine visual acuity using induction of normal physiological nystagmus, followed by an analysis and conclusion about the presence of nystagmus on specific presented optotypes. One of the key factors in the accuracy of visual acuity determination is the correct calculation of the size and movement of optotypes, which is analyzed in this review.